Konstruksi Sosial Masyarakat terhadap Pemandu Karaoke: Studi Kasus di Desa Botorejo Kecamatan Wonosalam Kabupaten Demak - Dewi Ratna Sari; Kuncoro Bayu Prasetyo (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2017)
Karaoke houses that many found in urban areas, nowadays also find into rural areas. The existence of karaoke houses can not be separated from the profession of